Morphology-dependent, green, and selective catalytic styrene oxidation on Co3O4 - Jain, Ruchi; Gopinath, Chinnakonda S. (Dalton Transactions, 2019)
Despite the great successes in the controlled fabrication of nanomaterials with specific composition and morphology, it is still challenging to have the desired control on the defect sites of catalyst materials. For unfolding the mystery of this aspect, catalytic styrene epoxidation was attempted on spinel Co3O4 with two different morphologies, namely, SNR (nanorods prepared by the solvothermal method with the (110) facet), HNR (nanorods prepared by the hydrothermal methodwith the (111) facet) and NC (nanocubes with the (110) facet) were synthesized and subjected to olefin oxidation with O-2. Even without any catalyst pretreatment, all three Co3O4 catalyst systems were found to be active for selective epoxidation of styrene with O-2 at ambient pressure in the liquid phase. The correlation between catalytic activity and selectivity trend suggests that the reaction is highly structure-sensitive and facile on the (110) facet. Temperature-dependent near ambient pressure X-ray photoelectron spectroscopy (NAPXPS) was carried out at 0.1 mbar O-2 pressure to understand the mechanistic aspects. The distinct catalytic activity of NC (110) and SNR (110) can be attributed to the population of defect sites on the catalyst surface. NC morphology with comparatively fewer defect sites shows high activity and selectivity, suggesting that styrene oxidation on Co3O4 is structure-sensitive; however, unlike metal surfaces, fewer defects are more favourable for catalytic styrene epoxidation due to facile adsorption and activation of the substrate and O-2 on Co3+ sites. The present investigations suggest that surface defects need not necessarily increase catalytic activity.